The Effect of Cooperative Jigsaw Learning Model Assisted by Maze Chase Game on Students’ Critical Thinking Skills - Dewi, Alfina Nur Karisma; Fatih, Mohamad; Oktaviani, Ragil Tri (Department of Primary School Teacher Education, Faculty of Teacher Training and Education, Jambi University, 2025)
This research is based on the low level of involvement and understanding of the material being taught, especially the material on plant body parts. This research aims to determine the effect and interaction between the Jigsaw cooperative learning model assisted by Maze Chase games on critical thinking skills. The method used is quantitative. The approach used is a pretest-posttest control group design. The test was carried out, showing that the control class significantly increased the critical thinking of students 0.00 < 0.05. Meanwhile, the experimental class was also proven to have provided an increase in thinking skills with significance 0.00 < 0.05. Then, the independent sample t-test shows a significant difference between the two learning models. It can be proven that ANOVA (two-way) obtains significance 0.00 < 0.05. The testing showed that learning with the Cooperative Jigsaw model, assisted by the Maze Chase game, has a posttest value higher than learning with the Cooperative Jigsaw model, even though the learning media are the same, and can improve students' critical thinking capabilities. The application of the jigsaw alone has been able to improve learning outcomes, but by combining Maze Chase, it has a stronger and more consistent influence.